2015
DOI: 10.15171/jnp.2016.05
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of plasma interleukin-18 concentration and severity of renal involvement and disease activity in systemic lupus erythematosus

Abstract: Background: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized by activation of T and polyclonal B lymphocytes. IL-18 was originally identified as a factor which enhances IFN-γ production and is a potent inducer of the inflammatory mediators by T cells, causing severe inflammatory disorders in SLE. Objectives: This study aimed to evaluate the association of plasma interlukine-18 (IL-18) concentration and severity of lupus nephritis (LN) and disease activity in SLE patients. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
4
17
0
3
Order By: Relevance
“…Finally, we demonstrated that NHBE cells exposed to both types of DEPs released IL-18, a key pro-inflammatory cytokine that works as a pleiotropic immune regulator by IFN-γ production, in the culture medium. Of note, IL-18 has been reported to play a potential pathological role in RA and SLE 60 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we demonstrated that NHBE cells exposed to both types of DEPs released IL-18, a key pro-inflammatory cytokine that works as a pleiotropic immune regulator by IFN-γ production, in the culture medium. Of note, IL-18 has been reported to play a potential pathological role in RA and SLE 60 64 .…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that PBMC from SSc patients with renal involvement produced less IL‐18 in response to stimulation with phytohaemagglutinin (PHA) compared to those without renal involvement . However, studies in other autoimmune conditions, such as SLE, strongly suggest a role for IL‐18 in renal disease . Future research examining the potential role of IL‐18 in renal, cardiac and pulmonary SSc manifestations on a larger prospective cohort would be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, studies in other autoimmune conditions, such as SLE, strongly suggest a role for IL-18 in renal disease. [26][27][28] Future research examining the potential role of IL-18 in renal, cardiac and pulmonary SSc manifestations on a larger prospective cohort would be worthwhile. Likewise, further studies investigating the molecular and cellular mechanisms by which IL-18 might regulate fibroblasts and fibrosis would be of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 is a potential pro-inflammatory cytokine. Although the involvement of IL-18 has been implicated in various diseases, especially autoimmune diseases, such as allergy and systemic lupus erythematosus 7 , 21 , only a few studies have demonstrated IL-18 regulation is involved in inflammatory myopathy 22 . We show that HIMF induces IL-18 expression in murine myoblasts through PDK1, which acts as a downstream effector in the PI3K/Akt/c-Jun signaling pathway and has been implicated in the regulation of neutrophil migration.…”
Section: Discussionmentioning
confidence: 99%